2020
DOI: 10.1021/acs.accounts.0c00419
|View full text |Cite
|
Sign up to set email alerts
|

Shining Light on Aluminum Nanoparticle Synthesis

Abstract: Conspectus Aluminum in its nanostructured form is generating increasing interest because of its light-harvesting properties, achieved by excitation of its localized surface plasmon resonance. Compared to traditional plasmonic materials, the coinage metals Au and Ag, Al is far more earth-abundant and, therefore, more suitable for large-area applications or where cost may be an important factor. Its optical properties are far more flexible than either Au or Ag, supporting plasmon resonances that range from UV wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 59 publications
(160 reference statements)
2
47
0
Order By: Relevance
“…[50] Owing to these merits, Al-based plasmonics has been increasingly studied for a wide variety of practical applications. [56][57][58][59][60][61] Nonetheless, one inherent limitation for Al crystals is the relatively broad linewidths of their SPs at visible frequencies due to their large radiative losses resulting from interband transitions. [62,63] Refractory metals including tungsten (W), tantalum (Ta), and molybdenum (Mo) have drawn substantial interest due to their high melting points (Figure 5C).…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] Owing to these merits, Al-based plasmonics has been increasingly studied for a wide variety of practical applications. [56][57][58][59][60][61] Nonetheless, one inherent limitation for Al crystals is the relatively broad linewidths of their SPs at visible frequencies due to their large radiative losses resulting from interband transitions. [62,63] Refractory metals including tungsten (W), tantalum (Ta), and molybdenum (Mo) have drawn substantial interest due to their high melting points (Figure 5C).…”
Section: Metalsmentioning
confidence: 99%
“…[ 50 ] Owing to these merits, Al‐based plasmonics has been increasingly studied for a wide variety of practical applications. [ 56–61 ] Nonetheless, one inherent limitation for Al crystals is the relatively broad linewidths of their SPs at visible frequencies due to their large radiative losses resulting from interband transitions. [ 62,63 ]…”
Section: Materials Selection and Nanostructured Designsmentioning
confidence: 99%
“…The Halas group demonstrated that aluminum (Al) nanostructures exhibit strong LSPRs in visible and ultraviolet regions of the electromagnetic spectrum . Halas group findings showed that Al nanostructures could perform a large number chemical transformations. ,, Furthermore, such nanostructures could be decorated by transition metals, which substantially broadens their catalytic properties . The Linic group discovered that copper nanoparticles (CuNPs) can be an excellent alternative to Au nanostructures in the photocatalysis of propylene to propylene oxide .…”
mentioning
confidence: 99%
“…12,14,15 Furthermore, such nanostructures could be decorated by transition metals, which substantially broadens their catalytic properties. 23 The Linic group discovered that copper nanoparticles (CuNPs) can be an excellent alternative to Au nanostructures in the photocatalysis of propylene to propylene oxide. 24 In this case, CuNPs provided a nearly 3 times higher selectivity of propylene oxide relative to the selectivity observed in a thermocatalytic catalysis.…”
mentioning
confidence: 99%
“…Most reported plasmonic Al nanostructures including Al thin films, , nanoparticles, , and nanovoids , have been fabricated using deposition coupled with lithography. Recently, Halas’s group reported a breakthrough in the synthesizing of Al nanocolloids, using a “bottom-up” approach in an argon-protected environment, and confirmed that Al nanocolloids have tunable optical resonance which shows great potential in surface-enhanced Raman applications for pollutant detection and photocatalytic reactivities. …”
Section: Introductionmentioning
confidence: 99%